Relationship Between Dairy Products Intake and Risk of Endometriosis: A Systematic Review and Dose-Response Meta-Analysis - Qi, Xiangying; Zhang, Wenyan; Ge, Mingxiu; Sun, Qiang; Peng, Lei; Cheng, Wenke; Li, Xuepeng (Frontiers in Nutrition, 2021)
Objective: Diet lifestyle can influence the risk of endometriosis. Therefore, we conducted a systematic meta-analysis to investigate the association between dairy products and the risk of endometriosis. Besides, we performed a dose-response meta-analysis to evaluate the amount of dairy intake affecting the risk of endometriosis. Methods: Relevant studies were searched from Pubmed, Embase databases, Cochrane Library, and Web of Science from the inception to November 6th, 2020. Also, the dose-response meta-analysis was conducted. All the pooled results were performed by risk ratios (RRs). Results: Finally, seven high-quality studies were included in the present meta-analysis. Total dairy intake was inversely associated with the risk of endometriosis, and the risk of endometriosis tended to decrease with a decrease in the risk of endometriosis when dairy products intake was over 21servings/week (RR0.87, 95%CI0.76-1.00; pnonlinearity=0.04). Similarly, people who consumed more than 18 servings of high-fat dairy products per week had a reduced risk of endometriosis (RR 0.86, 95%CI0.76-0.96). When stratified-analyses were conducted based on specific dairy product categories, it indicated that people with high cheese intake might have a reduced risk of endometriosis (RR 0.86, 95%CI0.74-1.00). Other specific dairy products such as whole milk (RR 0.90, 95%CI0.72-1.12), reduced-fat/skim milk (RR0.83, 95%CI0.50-1.73), ice cream (RR0.83, 95%CI0.50-1.73), and yogurt (RR0.83,95%CI0.62-1.11) have not shown significant evidence of an association with the risk of endometriosis. However, there is a higher risk of endometriosis in the females with high butter intake compared to females with low butter intake (1.27, 95%CI1.03-1.55). Conclusions: Overall, dairy products intake was associated with a reduction in endometriosis, with significant effects when the average daily intake≥3 servings. When analyzed according to the specific type of dairy product, it was shown that females with higher high-fat dairy and cheese intake might have a reduced risk of endometriosis. However, high butter intake might be associated to the increased risk of endometriosis. More future studies are needed to validate and add to this finding.